The Role of the Audit Board of Indonesia in Enhancing the Accountability of Regional Financial Management: A Literature Review - Pulungan, Irmayani; Nisa, Khairun; Jannah, Miftahul; Matondang, Khairani Alawiyah; Lubis, Putri Kemala Dewi (The Future of Education Journal, 2026)
This study examines the role of the Audit Board of Indonesia (BPK) in increasing the accountability of regional financial management through the audit functions, audit findings, and recommendations provided . Using a literature study method, this research analyzes various references such as scientific journals, books, and official BPK reports to provide a descriptive overview of regional financial oversight The results of the study show that BPK carries out operative functions through financial, performance, and specific purpose audits to assess the fairness of reports and the effectiveness of internal control systems . Audit findings., both related to weaknesses in the internal control system and non-compliance with regulations, are important indicators in assessing the quality of financial governance . The recommendations provided by BPK aim to encourage regional governments to improve systems, increase human resource capacity, and seriously follow up on findings in order to achieve better transparency and accountability